The Creative Dimensions Of Teaching Simple Song Composition To Students Of SMK Negeri 1 Ampelgading Pemalang - Alfira Arya Azhari; Nafik Salafiyah (Jurnal Seni Musik, 2024)
Student creativity is a key competency in the Merdeka Belajar curriculum. This study aims to describe the creative dimensions of teaching simple song composition in Grade X at SMK Negeri (State Vocational High School) 1 Ampelgading Pemalang using qualitative methods. Data were collected through observation, interviews, and documentation, validated using source triangulation, and analyzed through data reduction, data presentation, and conclusion drawing. The results show that the music education process at the school involves several stages: understanding the concepts of simple music, creating lyrics, composing simple orchestrations, and presenting the works in front of the class. This teaching process fosters original ideas, flexibility in thinking, and stimulates students; creativity.